Sensitivity of clumped isotope temperatures in fossil benthic and planktic foraminifera to diagenetic alteration - Leutert, Thomas J.; Sexton, Philip F.; Tripati, Aradhna; Piasecki, Alison; Ling Ho, Sze; Nele Meckler, A. (Geochimica et Cosmochimica Acta, 2019)
Applying the clumped isotope (Δ47) thermometer to foraminifer microfossils offers the potential to significantly improve paleoclimate reconstructions, owing to its insensitivity to the isotopic composition of seawater (unlike traditional oxygen isotope (δ18O) analyses). However, the extent to which primary Δ47 signatures of foraminiferal calcites can be overprinted during diagenesis is not well known. Here, we present Δ47 data as well as high-resolution (∼10 kyr) δ18O and δ13C middle Eocene time series, measured on benthic and planktic foraminifera from ODP/IODP Sites 1408, 1409, 1410, 1050, 1260 and 1263 in the Atlantic Ocean. The sites examined span various oceanographic regimes, including the western tropical to mid-latitude North Atlantic, and the eastern mid-latitude South Atlantic. Comparing data from contemporaneous foraminifera with different preservation states, we test the effects of diagenetic alteration on paleotemperature reconstructions for the deep and surface ocean. We find that overall, primary Δ47 signatures appear similarly sensitive to diagenetic overprinting as δ18O, with differences in sensitivity depending on pore fluid chemistry and the amount of secondary calcite. Where planktic foraminifera are significantly altered, sea surface temperatures derived from Δ47 and δ18O values are biased towards cool temperatures. In comparison, Δ47 and δ18O values of benthic and well preserved planktic foraminifera are less affected by diagenesis and thus likely to yield robust foraminiferal calcification temperatures. With independent estimates of diagenetic calcite fractions, secondary overprints could be corrected for, using end-member modeling and Δ47-based temperatures from benthic foraminifera.